Coolbox Design Modification for Traditional Fishing Vessel Using Sengon Wood Sawdust and Potassium Hydroxide-Soaked Coconut Coir - Ede Mehta Wardhana; Alam Baheramsyah; Hilmy Yassar (International Journal of Marine Engineering Innovation and Research, 2020)
This research modified coolbox by mixing sengon wood sawdust and potassium hydroxide-soaked cocofiber. By considering its composition, potassium hydroxide content, and soaking duration, this research was done to find the optimum amount of those three variables to make the best insulator. The best insulator was chosen based on its thermal conductivity, density, and economic value, and the easiness in the making. From the experiment, the chosen composition consists of 30% sengon wood sawdust and 70% potassium hydroxide-soaked cocofiber with content of 15% and soaking duration of 2 hours. With thermal conductivity of 0,352W/mK, density of 0,303gram/cm3, and specimen production cost of Rp607,41, this material was used for composition reference in the making of the coolbox. The experiment of coolbox lasted for 35 hours with 71 temperature data retrievals. The coolbox experiment used 500 gram tuna fish and 2500 gram ice as cooler. The result showed that the lowest temperature for ice inside coolbox was 0,3°C, the lowest temperature of fish was 5°C, and the lowest temperature in coolbox chamber is 17°C. With the ratio of 1:5 for fish and ice, the coolbox insulation using sengon wood sawdust and potassium hydroxide-soaked cocofiber was able to maintain fish temperature below 20°C for 27,5 hours. Meanwhile, the styrofoam coolbox was able to maintain fish with the same condition for 35 hours.